Altered Resting-State Brain Activity in Schizophrenia and Obsessive-Compulsive Disorder Compared With Non-psychiatric Controls: Commonalities and Distinctions Across Disorders - Zhang, Yuyanan; Liao, Jinmin; Li, Qianqian; Zhang, Xiao; Liu, Lijun; Yan, Jun; Zhang, Dai; Yan, Hao; Yue, Weihua (Frontiers in Psychiatry, 2021)
Backgrounds: Schizophrenia (SCZ) and obsessive-compulsive disorder (OCD) are classified as two chronic psychiatric disorders while showed high comorbidity rate and shared clinical symptoms. Abnormal spontaneous brain activity within the cortical-striatal neural circuits has been observed in both of them. However, it is unclear the common or distinct neural abnormalities underlie the neurobiological substrates in the resting state. Methods: Resting-state fMRI data was collected from 88 patients with SCZ, 58 patients with OCD and 72 healthy control subjects. First, we examined differences in amplitude of low-frequency fluctuations (ALFF) among three groups. Resting-state functional connectivity (rsFC) analysis with the brain region that showed different ALFF as the seed was then conducted to identify the changes in brain networks. Finally, we examined the correlation between the altered activities and clinical symptoms. Results: Both the patients with SCZ and OCD showed increased ALFF in the right hippocampus and decreased ALFF in the left posterior cingulate cortex (PCC). SCZ patients exhibited increased ALFF in the left caudate (voxel-level FWE P < 0.05) and decreased rsFC between the left caudate and right cerebellum that correlated with positive symptoms. Left caudate showed increased rsFC with right thalamus and bilateral supplementary motor complex (SMC) respectively in OCD patients (cluster-level FWE P < 0.05). Conclusions: Hippocampus and PCC are common regions presenting abnormal local spontaneous neuronal activities in both SCZ and OCD, while the abnormality of striatum can reflect the differences. Increased ALFF in the striatum and symptom-related weakened rsFC between caudate and cerebellum showed SCZ-specificity. Enhanced rsFC between caudate and SMC may be a key characteristic in OCD. Our research shows the similarities and differences between the two diseases from the perspective of resting-state fMRI, which provides clues to understand the disease and find methods for treatment.